2012
DOI: 10.1016/j.physbeh.2011.11.023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise on the neuronal response to food cues

Abstract: Increased physical activity is associated with successful long-term weight loss maintenance due to mechanisms likely more complex than simply increased energy expenditure. The impact of physical activity on the central regulation of food intake may be an important mechanism of this effect. The objective of this study was to examine the effects of exercise training and acute exercise on the neuronal response to food cues as well as eating behaviors. fMRI was performed in the fasted state at baseline and again a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
119
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 57 publications
13
119
0
1
Order By: Relevance
“…We found that aerobic exercise, compared to the rest condition, reduced the neuronal response in food reward (i.e., insula, orbitofrontal cortex, putamen, rolandic operculum) and visual attention (i.e., inferior and middle occipital gyrus) brain regions. This is consistent with a recent study [61] showing that chronic exercise (40-60 minutes/day for 6 months) lowered the neuronal response in the insula (food reward region) in overweight/obese individuals. Thus, these data suggest that both acute and chronic aerobic exercise reduces neuronal responses in food reward and visual attention brain regions, consistent with reducing the pleasure and palatability of food, incentive motivation to eat, and anticipation and consumption of food In exploratory analyses (unpublished observation), we recently assessed exercise-induced changes in neuronal responses in men and women analyzed separately.…”
Section: Exercise and Neuronal Responsessupporting
confidence: 93%
“…We found that aerobic exercise, compared to the rest condition, reduced the neuronal response in food reward (i.e., insula, orbitofrontal cortex, putamen, rolandic operculum) and visual attention (i.e., inferior and middle occipital gyrus) brain regions. This is consistent with a recent study [61] showing that chronic exercise (40-60 minutes/day for 6 months) lowered the neuronal response in the insula (food reward region) in overweight/obese individuals. Thus, these data suggest that both acute and chronic aerobic exercise reduces neuronal responses in food reward and visual attention brain regions, consistent with reducing the pleasure and palatability of food, incentive motivation to eat, and anticipation and consumption of food In exploratory analyses (unpublished observation), we recently assessed exercise-induced changes in neuronal responses in men and women analyzed separately.…”
Section: Exercise and Neuronal Responsessupporting
confidence: 93%
“…In support of the current results, increases in fat mass over a 6-mo period were associated with increases in responsivity to palatable food images in visual processing/attention and gustatory regions relative to baseline (39). In addition, behavioral data indicated that individuals randomly assigned to consume energydense foods for 2-3-wk periods showed an increased willingness to work (ie, incentive for those foods) (40,41).…”
Section: Discussionsupporting
confidence: 80%
“…Some studies have shown that subjective appetite in the fasted state is increased after exercise training [40][41][42], whereas others have reported no change [43][44][45] or even a reduction in appetite [46]. Furthermore, exercise training has been shown in some studies to have negligible effects on energy or macronutrient consumption [9,43,47,48], while others have demonstrated that energy intake is reduced [49] and protein intake is elevated [45] after training.…”
Section: Chronic Exercisementioning
confidence: 99%